The long divergence : how Islamic law held back the Middle East - Kuran, Timur (Princeton University Press, 2011)
In the year 1000, the economy of the Middle East was at least as advanced as that of Europe. But by 1800, the region had fallen dramatically behind--in living standards, technology, and economic institutions. In short, the Middle East had failed to modernize economically as the West surged ahead. What caused this long divergence? And why does the Middle East remain drastically underdeveloped compared to the West? In The Long Divergence, one of the world's leading experts on Islamic economic institutions and the economy of the Middle East provides a new answer to these long-debated questions. T.